Application of Value Engineering in Lecture Buildings (Case Study Joint Lecture Building, Campus C, Airlangga University, Surabaya) - Sayyidah, Nabila Hadi (Faculty of Civil Engeneering and Planning - ITATS, 2024)
ver time, construction projects in Indonesia as a developing country have become increasingly complex and require large costs and require more attention to proper time and resource management. The Joint Lecture Building, Campus C, Airlangga University, Surabaya, with a project cost of IDR 8,300,000.00/m2 is considered to exceed the standard cost of similar buildings in Surabaya, which is IDR 6,250,000.00/m², so it requires a cost efficiency evaluation. This study uses a value engineering method by analyzing work items to find alternative materials that are more cost-effective without reducing function and quality. This study was conducted with five stages of value engineering: information, creativity, analysis, development, and recommendations. The results show significant cost savings on several work items such as beam work, floor slabs and columns, achieving a potential reduction of up to 71% of the total existing budget.